Disgust lowers olfactory threshold: a test of the underlying mechanism. Issue 3 (2nd April 2020) - Chan, Kai Qin; van Dooren, Roel; Holland, Rob W.; van Knippenberg, Ad
ABSTRACT: The olfactory system provides us with rich information about the world, but the odours around us are not always detectable. Previous research has shown that disgust enhances olfactory sensitivity to n -butanol. Because n -butanol incidentally is mildly negative, it is unclear whether disgust, being a negative, avoidant emotion, enhances sensitivity to stimuli with negative qualities (valence-fit effect), or across stimuli in general (general sensitivity effect). Here we tested these competing hypotheses by examining thresholds to two scents, one positive (phenylethanol) and one mildly negative ( n -butanol), during a disgust, happiness, and neutral emotion induction. We found that exposure to disgusting pictures lowered olfactory threshold across both scents. Thus our current results replicated the results of previous research, and also revealed support for a general sensitivity rather than a valence-fit effect. This suggests that disgust facilitates the perceptual detection of extremely faint targets presumably because avoidant emotions enhance perceptual vigilance in general.